Controlled ovarian hyperstimulation for poor ovarian responders undergoing in vitro fertilisation/intracytoplasmic sperm injection: a protocol for systematic review and Bayesian network meta-analysis. Issue 2 (23rd February 2021) - Yang, Huisheng; Zheng, Chensi; Zheng, Qiyan; Xu, Huanfang; Li, Xiaotong; Hao, Mingzhao; Fang, Yigong
Abstract : Introduction: Controlled ovarian hyperstimulation (COH) is the routine regimen used to generate a sufficient number of follicles during in vitro fertilisation (IVF) or intracytoplasmic sperm injection (ICSI) treatment. Poor ovarian response is a challenge encountered by many clinicians during COH and poor ovarian responders (PORs) usually have higher follicle stimulating hormone levels, lower levels of anti-Mullerian hormone and few oocytes retrieved, which have been attributed mainly to advanced maternal age and poor follicle reserve or other reasons that could impair ovarian response during ovarian stimulation. Over the last few decades, researchers have proposed a series of strategies and ovarian stimulation protocols to improve pregnancy outcomes in patients with POR during their IVF/ICSI treatment. However, clinical decisions regarding COH protocols in PORs during IVF/ICSI treatment remain controversial. Traditional pairwise meta-analysis only allows the direct comparison of two protocols in COH for patients with POR. However, many of these COH protocols have not been compared directly in randomised controlled trials (RCTs). Thus, we aim to use network meta-analysis (NMA) to assess the clinical effectiveness and safety of COH protocols and to generate treatment rankings of these COH protocols for the most clinically important and commonly reported outcomes events. Methods and analysis: The PubMed, Embase, Cochrane Library, Web of Science, SinoMed, CNKI, WanFang database and Chongqing VIP information databases will be searched for all RCTs of COH for POR women during IVF/ICSI from inception to 31 March 2020. Primary outcomes will include live birth rate and number of oocytes retrieved. Secondary outcomes will include ongoing pregnancy rate, clinical pregnancy rate, miscarriage rate, ovarian hyperstimulation syndrome rate, multiple pregnancy rate and cycle cancellation rate. Pairwise meta-analysis and Bayesian NMA will be conducted for each outcome. Subgroup analysis, meta-regression, and sensitivity analysis will be performed to assess the robustness of the findings. The generation of NMA plots and subsequent results will be performed by using R V.4.0.1. The assessment of confidence in network estimates will use the Confidence in Network Meta-Analysis)web application (see https://cinema.ispm.unibe.ch/ ). Ethics and dissemination: This review does not require ethics approval and the results of the NMA will be submitted to a peer-review journal.